A Peer-to-Peer Live-Streaming Intervention for Children During COVID-19 Homeschooling to Promote Physical Activity and Reduce Anxiety and Eye Strain: Cluster Randomized Controlled Trial - Zheng, Yingfeng; Wang, Wei; Zhong, Yuxin; Wu, Fengchun; Zhu, Zhuoting; Tham, Yih-Chung; Lamoureux, Ecosse; Xiao, Liang; Zhu, Erta; Liu, Haoning; Jin, Ling; Liang, Linyi; et al. (JMIR Publications, 2021)
BackgroundThe COVID-19 pandemic has led to worldwide school closures, with millions of children confined to online learning at home. As a result, children may be susceptible to anxiety and digital eye strain, highlighting a need for population interventions. ObjectiveThe objective of our study was to investigate whether a digital behavior change intervention aimed at promoting physical activity could reduce children's anxiety and digital eye strain while undergoing prolonged homeschooling during the COVID-19 pandemic. MethodsIn this cluster randomized controlled trial, homeschooled grade 7 students at 12 middle schools in southern China were recruited through local schools and randomly assigned by the school to receive (1:1 allocation): (1) health education information promoting exercise and ocular relaxation, and access to a digital behavior change intervention, with live streaming and peer sharing of promoted activities (intervention), or (2) health education information only (control). The primary outcome was change in self-reported anxiety score. Secondary outcomes included change in self-reported eye strain and sleep quality. ResultsOn March 16, 2020, 1009 children were evaluated, and 954 (94.5%) eligible children of consenting families were included in the intention-to-treat analysis. Children in the intervention (n=485, 6 schools) and control (n=469, 6 schools) groups were aged 13.5 (SD 0.5) years, and 52.3% (n=499) were male. The assigned interventions were completed by 896 children (intervention: n=467, 96.3%; control: n=429, 91.5%). The 2-week change in square-root-transformed self-reported anxiety scores was greater in the intervention (-0.23, 95% CI -0.27 to -0.20) vs control group (0.12, 95% CI 0.09-0.16; unadjusted difference -0.36, 95% CI -0.63 to -0.08; P=.02). There was a significant reduction in square-root-transformed eye strain in the intervention group (-0.08, 95% CI -0.10 to 0.06) compared to controls (0.07, 95% CI 0.05-0.09; difference -0.15, 95% CI -0.26 to -0.03; P=.02). Change in sleep quality was similar between the two groups. ConclusionsThis digital behavior change intervention reduced children's anxiety and eye strain during COVID-19-associated online schooling. Trial RegistrationClinicalTrials.gov NCT04309097; http://clinicaltrials.gov/ct2/show/NCT04309097